2000
DOI: 10.1063/1.126171
|View full text |Cite
|
Sign up to set email alerts
|

Improved characteristics of InGaN multiple-quantum-well light-emitting diode by GaN/AlGaN distributed Bragg reflector grown on sapphire

Abstract: An InGaN multiple-quantum-well light-emitting diode (LED) containing a GaN/AlGaN distributed Bragg reflector has been grown on a sapphire substrate by metalorganic chemical vapor deposition. Comparing with the conventional LED, the output power has been improved from 79 to 120 μW under 20 mA direct current biasing condition and the external quantum efficiency has been also improved from 0.16% to 0.23% under 10 mA dc current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 9 publications
1
63
0
Order By: Relevance
“…When AlGaN aluminium content is in the range [40%…60%] [32][33][34][35], the reflectivities are comparable with those of LM AlInN/GaN DBRs (so are the refractive index contrasts) as far as the number of pairs does not exceed 20 to 30, i.e. for moderate reflectivity DBRs.…”
Section: Feature Articlementioning
confidence: 60%
“…When AlGaN aluminium content is in the range [40%…60%] [32][33][34][35], the reflectivities are comparable with those of LM AlInN/GaN DBRs (so are the refractive index contrasts) as far as the number of pairs does not exceed 20 to 30, i.e. for moderate reflectivity DBRs.…”
Section: Feature Articlementioning
confidence: 60%
“…The insertion of a distributed Bragg reflector (DBR) between the active layer and the substrate contributes to the enhancement of the optical output power of a LED. Nakada et al reported that considerably higher output power was obtained from a GaInN LED after inserting a DBR between the LED structure and sapphire substrate [1]. Since thin-film laser lift-off (LLO) techniques have recently been developed [2][3][4], GaN-based LEDs fabricated on reflective-metal-mirrorcoated Si substrates by transferring the LED structures from sapphire substrates have been demonstrated [5].…”
Section: Introductionmentioning
confidence: 98%
“…While AlN/GaN DBRs have been reported 14 , epitaxial growth considerations usually limit the Al fraction to between 0.25 and 0.4 15,16 . In the light of this limitation the performance of a RCLED structure incorporating a 9 period Al 0.3 Ga 0.7 N/GaN DBR and a single QW active region was further investigated.…”
Section: Critical Design Parametersmentioning
confidence: 99%